Hyundai Motor Company’s overseas manufacturing policy :|the analysis of Turkey as a production site - Uçar, Kuntay Yiğit. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
By the 1980s, the dominance globalization was felt on the world economy. Large companies in developed countries have started to make overseas investments in order to make more profit, consequently they have turned into multinational companies. Developing countries also need to have some qualifications to attract these investments in to their own countries for economic development and stability. Foreign direct investments have effects on many macroeconomic indicators such as employment, exports, balance of payments, production, and inflation of the host country. Due to the understanding of the importance of these investments in Turkey by 1970s, foreign direct investments on Turkish Automotive Sector started. Automotive sector has a key role on economic development for both developed and emerging countries. It is known that automotive sector has a very important place for the Turkish economy. Foreign capital investments on automotive sector played an important role for the growth of the Turkish economy. In this context, it has become necessary to conduct more studies on foreign capital investments made in automotive industry, which can be seen as the locomotive sector of country's economy. In this thesis, the development and growth of the Turkish Automotive Industry with foreign capital investments has been examined in light of the investments made by South Korean Hyundai Motors Company in Turkey. In addition, the effects of Hyundai Assan joint venture on country's economy and the results of these effects in terms of economy, politics and social areas are examined.
Keywords: Automobile industry and trade -- Turkey.